Analisis Kesalahan-Kesalahan Gramatikal Dalam Tulisan Bahasa Inggris Mahasiswa Pendidikan Guru Sekolah Dasar FIP UNM - Sidrah Afriani Rachman; Rival Rival; Haerul Haerul (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
This study aims to reveal the errors of students in the practice of writing English, especially errors in any aspect of the language and how often its frequency. The researcher analyzes the errors of the English writings of PGSD students taking English courses. This analysis uses Surface Strategy Taxonomy in classifying student errors in grammatical structures. This research uses descriptive research method with a qualitative approach. The subject of this research was the writing of sixth semester students who were respondents and attended the English for Specific Purpose 2017/2018 school year totaling 75 people. The results of this study indicate that students' mistakes in producing English writing are divided into several categories of errors, namely errors in formation (misformation), errors in omission (addition), errors in addition (addition), and errors in preparation (misordering). The most frequently made mistake is error formation in sentences that is 181 or around 44.80% of the total number of student writing errors. Omission (omission) occurred as many as 136 or 33.66%, followed by misordering 48 times or 11.88% and the least was an addition error of 39 times or 9.65%.